2007
DOI: 10.1093/rheumatology/kem101
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of infliximab in refractory posterior uveitis of Behcet's disease: a 24-month follow-up study

Abstract: Infliximab is rapidly effective and safe in a high proportion BD patients with refractory posterior uveitis, and may be helpful to prevent recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(77 citation statements)
references
References 21 publications
3
68
0
6
Order By: Relevance
“…IFX and ADA, however, remain the drug of choice for patients with uveitis. We have opted to use regularly scheduled IFX infusion as the main first-line biological therapy option in the majority of our patients because of its proven dramatic sustained efficacy in previous studies, especially for uveitis associated with BD (31)(32)(33)(34). In comparison to the 2008 EULAR recommendations that suggested IFX be used as a combination or add-on therapy with azathioprine in refractory eye involvement, our patients who presented with uveitis were treated early with IFX as monotherapy and had favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…IFX and ADA, however, remain the drug of choice for patients with uveitis. We have opted to use regularly scheduled IFX infusion as the main first-line biological therapy option in the majority of our patients because of its proven dramatic sustained efficacy in previous studies, especially for uveitis associated with BD (31)(32)(33)(34). In comparison to the 2008 EULAR recommendations that suggested IFX be used as a combination or add-on therapy with azathioprine in refractory eye involvement, our patients who presented with uveitis were treated early with IFX as monotherapy and had favorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study confirms what has already been reported for Behc¸et's disease patients with shorter term follow-up on infliximab. [19][20][21] Recently, we have shown that infliximab therapy significantly reduced retinal vascular leakage scores at 12 months compared with the baseline. 14 In the present study, we confirmed the sustained effect of infliximab on suppressing background vascular leakage over 4 years, although it took B2 years for vascular leakage scores to reach their lowest level.…”
Section: Discussionmentioning
confidence: 99%
“…No safety problems were noted. Niccoli et al (2007) assessed the efficacy of infliximab 5mg/kg (9 infusions) plus prednisolone 1mg/kg over a long-term follow-up (24 months) in 12 consecutive patients with refractory posterior uveitis. A rapid response was noted after first infusion.…”
Section: Eye Diseasementioning
confidence: 99%